Immunogenicity of the Plasmodium falciparum serine repeat antigen (p126) expressed by vaccinia virus. - Tine, J A (1993)
cDNA encoding the serine repeat antigen (SERA) (also called p126) of Plasmodium falciparum has been isolated from the FCR3 strain and inserted into a recombinant vaccinia virus designated vP870. Expression analysis of vP870-infected Vero cells by immunoprecipitation has demonstrated several intracellular forms of SERA and a single secreted SERA peptide. Endoglycosidase digestion of these immunoprecipitated SERA peptides indicated that the intracellular SERA peptides contain simple, high-mannose N-linked oligosaccharides and that the secreted SERA peptide contains complex N-linked oligosaccharides. Pulse-chase experiments indicate that the multiple intracellular SERA peptides in infected Vero cells represent a trafficking pathway whereby the smallest SERA peptide is converted into larger peptides by co- and posttranslational modifications, including glycosylation, and eventually secreted from the cell with complex N-linked oligosaccharides. To study the immunogenicity of vaccinia virus-expressed SERA, rabbits were immunized with vP870 and their sera were analyzed for reactivity with authentic, parasite-derived SERA protein. The anti-vP870 rabbit sera reacted with P. falciparum-infected erythrocytes by immunofluorescence analysis, recognized authentic SERA from schizonts by both immunoprecipitation and Western blot (immunoblot) analyses, and recognized proteolytically processed fragments of SERA secreted into the culture medium by Western blot analysis. These results indicate that when expressed by vaccinia virus, SERA is glycosylated and secreted from infected cells and that in immunized rabbits, vaccinia virus-expressed SERA can stimulate a humoral immune response against SERA derived from blood-stage parasites.